2014
DOI: 10.1371/journal.pone.0100668
|View full text |Cite
|
Sign up to set email alerts
|

Leaf and Root-Associated Fungal Assemblages Do Not Follow Similar Elevational Diversity Patterns

Abstract: The diversity of fungi along environmental gradients has been little explored in contrast to plants and animals. Consequently, environmental factors influencing the composition of fungal assemblages are poorly understood. The aim of this study was to determine whether the diversity and composition of leaf and root-associated fungal assemblages vary with elevation and to investigate potential explanatory variables. High-throughput sequencing of the Internal Transcribed Spacer 1 region was used to explore fungal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
88
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(102 citation statements)
references
References 49 publications
13
88
1
Order By: Relevance
“…Recently, it was shown that the composition of leaf-associated fungi on F. sylvatica is correlated primarily with the annual mean temperature (Cordier et al 2012, Coince et al 2014. In the present work, the detection B. nummularia DNA in symptomless tissue of beech showed a significant decreasing trend as the mean precipitation of the month preceding the sampling increases (R 2 = 0.86), i.e., the amount of latent infection increased with decreasing precipitation.…”
Section: Discussionsupporting
confidence: 56%
“…Recently, it was shown that the composition of leaf-associated fungi on F. sylvatica is correlated primarily with the annual mean temperature (Cordier et al 2012, Coince et al 2014. In the present work, the detection B. nummularia DNA in symptomless tissue of beech showed a significant decreasing trend as the mean precipitation of the month preceding the sampling increases (R 2 = 0.86), i.e., the amount of latent infection increased with decreasing precipitation.…”
Section: Discussionsupporting
confidence: 56%
“…Bryant et al (2008) found that Acidobacteria decreased in richness over a change of 1000 m elevation in the Rocky Mountains. Similarly mixed results have been found for Fungi, with evidence for greatest richness at mid-elevations due to range overlap (Bahram et al 2012, Coince et al 2014, Miyamoto et al 2014, lack of change with elevation (Zimmerman and Vitousek 2012, Coince et al 2014, Jarvis et al 2015, decreased richness at higher elevations (Looby et al 2016), or increased richness at higher elevations (Pellissier et al 2014). Fewer studies have examined Archaea, but work on two Japanese mountains found a mid-elevation peak in OTU richness (Singh et al 2012, Singh et al 2016).…”
Section: Controls Over Microbial Richnessmentioning
confidence: 91%
“…By opening the microbial world to ecologists, the next-gen revolution also gave rise to larger scale studies, aimed at assessing the influence of climate and other global change components on tree-associated microbial communities. The analysis of beech-associated fungal communities along elevation gradients suggested that the air temperature is a major structuring factor of foliar communities (Cordier et al 2012b) but not of their below-ground counterparts (Coince et al 2014). A comparison between urban and non-urban stands revealed significant effects of anthropogenic activities on foliar fungal communities of Quercus macrocarpa (Jumpponen and Jones 2010).…”
Section: Trees Are Holobiontsmentioning
confidence: 97%